2006
DOI: 10.1038/sj.bjc.6603007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 A870G polymorphism and the risk of colorectal cancer and adenoma

Abstract: Cyclin D1 (CCND1) plays a key role in cell cycle control, particularly in the transition from G 1 to S phase, which is regulated by cyclindependent kinases. A common adenine to guanine polymorphism (A870G) in the CCND1 gene has been associated with a longer-life protein and an increased risk of colorectal cancer and adenoma in some studies. Among subjects with hereditary nonpolyposis colorectal cancer, the A870G polymorphism has also been associated with a younger age of onset of colorectal cancer. We analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
23
2
Order By: Relevance
“…Heterogeneity was explored using subgroup analysis (10) with ethnicity (Asians and Caucasians) and cancer types. We have classified the cancer types in nine different categories including breast (13)(14)(15)(16)(17)(18)(19), colorectal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), gynecologic [ovarian (35), cervical (36), and endometrial (37)], digestive tract [oral (38)(39)(40), esophageal (41)(42)(43)(44), and stomach (45,46)], blood-related [acute lymphoblastic leukemia (47), mantle cell lymphoma (48), and non-Hodgkin's lymphoma (49)], genitourinary [bladder (50)(51)(52)(53), prostate (54,55), and kidney (56)], lung (57)(58)(59)…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity was explored using subgroup analysis (10) with ethnicity (Asians and Caucasians) and cancer types. We have classified the cancer types in nine different categories including breast (13)(14)(15)(16)(17)(18)(19), colorectal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), gynecologic [ovarian (35), cervical (36), and endometrial (37)], digestive tract [oral (38)(39)(40), esophageal (41)(42)(43)(44), and stomach (45,46)], blood-related [acute lymphoblastic leukemia (47), mantle cell lymphoma (48), and non-Hodgkin's lymphoma (49)], genitourinary [bladder (50)(51)(52)(53), prostate (54,55), and kidney (56)], lung (57)(58)(59)…”
Section: Methodsmentioning
confidence: 99%
“…Since PEST domain is critical for the protein degradation, 870A allele encoded protein has a longer half-life than its wild type variant. As a result, it is suggested that individuals with CCDN1 870A allele can more easily bypass G1-S checkpoint and more likely to develop cancer (Betticher et al, 1995;Weinstein et al, 1997;Sawa et al, 1998;Solomon et al, 2003;Schernhammer et al, 2006). This hypothesis has been tested in various cancer types with variable results.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Also, carriers of the A allele appear to be more frequent among individuals who developed non-syndromic colorectal cancer before the age of 60, 10 subjects with familial colorectal cancer 11,12 and affected women. 13,14 Other reports, however, do not subscribe to rs9344 genotype being a modifier of the colorectal cancer phenotype. 15,16 Given the low odds ratios (OR) associated with common variants, such as rs9344, we have argued that genetic risk factors underlying complex diseases are more likely to be due to functionally relevant rare variants with moderate penetrance that will considerably increase susceptibility and will, therefore, sometimes justify prophylactic interventions.…”
Section: Introductionmentioning
confidence: 99%